A cross-sectional network analysis of successful aging in a resilience-based framework - Lotte P. Brinkhof; K. Richard Ridderinkhof; Sanne de Wit; Harm J. Krugers; Jaap M. J. Murre (PLoS ONE, 2025)
Aging inevitably gives rise to many challenges and transitions that can greatly impact our (mental) well-being and quality of life if these are not controlled adequately. Hence, the key to successful aging may not be the absence of these stressors, but the ability to demonstrate resilience against them. The current study set out to explore how resilience and successful aging may intersect by investigating how various resilience capacity-promoting (protective) and resilience capacity-reducing (risk) factors relate to mental well-being and quality of life. Through a large-scale (N = 2000, age 55+, 30 factors) network analysis, we established the interplay between risk/protective factors from various domains, including demographics, (mental) health, (environmental) stress, lifestyle, coping/personality, and ageism. We revealed some unique pathways through which each of these factors contribute to individuals’ mental well-being and/or quality of life, and interpreted these findings in terms of a resilience-based framework of successful aging. Our findings emphasize the complexity of factors that can impact quality of life and mental well-being in later life and can steer researchers and practitioners in devising efficacious, multi-pronged interventions that target risk and protective factors simultaneously, thereby maximizing their potential in boosting beneficial outcomes among older individuals.